2011
DOI: 10.1371/journal.pone.0017569
|View full text |Cite
|
Sign up to set email alerts
|

HLA Genes, Islet Autoantibodies and Residual C-Peptide at the Clinical Onset of Type 1 Diabetes Mellitus and the Risk of Retinopathy 15 Years Later

Abstract: Aims/HypothesisHLA genes, islet autoantibodies and residual C-peptide were studied to determine the independent association of each exposure with diabetic retinopathy (DR), 15 years after the clinical onset of type 1 diabetes in 15–34 year old individuals.MethodsThe cohort was identified in 1992 and 1993 by the Diabetes Incidence Study in Sweden (DISS), which investigates incident cases of diabetes for patients between 15 and 34 years of age. Blood samples at diagnosis were analyzed to determine HLA genotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 79 publications
1
17
1
3
Order By: Relevance
“…For example, GAD levels in patients with newly diagnosed T1D were associated with worse peripheral nerve function, independent of GAD-related differences in glycemic control. 32 In addition, anti-GAD antibodies levels at the onset of T1D increased the risk of diabetic retinopathy 15 years later; 33 thus, we should stress the importance of detecting anti-GAD Nomogram for patients with newly diagnosed type 1 diabetes. To use the nomogram, the value attributed to an individual patient is located on each variable axis, and a line is drawn upwards to determine the number of points awarded for each variable.…”
Section: Tablementioning
confidence: 99%
“…For example, GAD levels in patients with newly diagnosed T1D were associated with worse peripheral nerve function, independent of GAD-related differences in glycemic control. 32 In addition, anti-GAD antibodies levels at the onset of T1D increased the risk of diabetic retinopathy 15 years later; 33 thus, we should stress the importance of detecting anti-GAD Nomogram for patients with newly diagnosed type 1 diabetes. To use the nomogram, the value attributed to an individual patient is located on each variable axis, and a line is drawn upwards to determine the number of points awarded for each variable.…”
Section: Tablementioning
confidence: 99%
“…It is well established that other islet autoantibodies such as insulin autoantibodies and phogrin are highly accurate T1D risk predictors in childhood [46] and the age of detection of insulin autoantibodies in particular, exhibits close associations with age of T1D diagnosis in children [39]. In contrast, the presence of autoantibodies against GAD65 appears to be related to adult ages and also it has been reported that high GAD65 antibody titers exhibit a correlation with longer-term diabetic complications such as retinopathy, 15 years after T1D onset [47]. …”
Section: Clinical Relevance For T1d Diagnosismentioning
confidence: 99%
“…Although less prevalent than type 2 (T2) diabetes (T2D), T1D usually strikes pediatric as mainly affects young patients, and strictly requires exogenous insulin supplementation. Unfortunately, though a life-saving therapy, exogenous insulin may delay but not eliminate the risk for developing secondary, chronic complications of the disease [2]. T1D is notoriously caused by autoimmune destruction of pancreatic islet β-cells.…”
Section: Introductionmentioning
confidence: 99%